The Impacts of Protein Supplementation and Semen Exposure on Uterine Cytokines in Beef Heifers - Kyle J. McLean; Kiernan J. Brandt; Taylor B. Ault-Seay; Rebecca R. Payton; Liesel G. Schneider; J. Lannett Edwards; Phillip R. Myer; Justin D. Rhinehart (Agriculture)
Reproductive efficiency is largely impacted during heifer development, which generally requires nutrient supplementation for proper maturation. Nutritional status can also influence inflammation within the reproductive tract. Therefore, we hypothesized that cytokine concentrations in uterine luminal fluid (ULF) will be impacted by protein supplementation following exposure to semen via artificial insemination (AI). Commercial heifers (n = 60) were utilized to determine the effects of protein supplementation and AI on cytokine concentrations in ULF. Heifers were randomly assigned to one of three crude protein (CP) treatments (11%, 15%, and 19% overall CP) via supplementation: (1) CON (10% CP), (2) P20 (20% CP), and (3) P40 (40% CP). All heifers underwent estrus synchronization and ULF was collected 14 d after insemination. Cytokine profiles were constructed in MetaboAnalyst 5.0, and R Studio was used for individual cytokine analyses. Control heifers had increased (p = 0.05) MIP-1β concentrations (148.7 ± 123.9 pg) over P20 heifers (42.3 ± 123.9 pg), and P40 heifers (75.5 ± 123.9 pg) had intermediate concentrations. Semen exposure (1877 ± 550 pg) showed a trend (p = 0.06) to increase concentrations of IP-10 compared with heifers who were not inseminated (1556 ± 550 pg). In conclusion, although protein supplementation and semen exposure had minimal effects on overall cytokine profiles, MIP-1β, IP-10, and MIP-1α were identified as potential key regulators of uterine inflammation during early gestation.